Creación de restaurante de comida mediterránea con influencia colombiana cuyos empleados serán actores del conflicto en Colombia (2020)
Informal work and labor neglect by the Colombian state towards the actors of the armed conflict in Colombia is the main driver of this project. According to Patricia Linares, former president of the Special Jurisdiction for Peace, if those appearing who committed crimes do not have opportunities from the moment they fulfill their commitments to the law, there is no social reconciliation. According to her, these should be productive and a hand should be extended to them so that they can reform themselves and not return to violence and become part of armed groups to find income that was denied them in other institutions due to their status as ex-combatants. appearing and / or their criminal record. The creation of Luz Marina S.A.S. seeks to help with the reintegration and reincorporation of these people into society through the offer of a decent job together with psychosocial support. When both victims and appearing parties work in the same environment, social reconciliation will be supported at different levels.